AKTIVITAS ANTIMIKROBA EKSTRAK ETANOL BATANG WOLE WOE ASAL HALMAHERA TENGAH TERHADAP BAKTERI GRAM POSITIF Staphylococcus epidermidis DAN Staphylococcus aureus - Fitriana Fitriana; Sitti Amirah; Safriani Rahman (Fakultas Farmasi UMI, 2022)
The wole woe plant is one of the plants empirically used by the Weda community in Central Halmahera district as a traditional medicine to treat various diseases such as breast cancer, cysts, vaginal discharge, diabetes mellitus, wounds, dysentery, cholesterol, and gout. Therefore, a study was conducted on the antimicrobial activity of the ethanolic extract of wole woe stems against gram-positive bacteria S. epidermidis and S. aureus with the aim of determining the concentration that provides antimicrobial activity of the ethanolic extract of wole woe stems by using the agar diffusion method. The results obtained in the screening test gave activity at a concentration of 0.1% and the results of the minimum inhibitory concentration test (MIC) and the minimum killing concentration test (MBC) obtained a MIC value of 1.6% for S. epidermidis bacteria and 0.8% for S. aureus bacteria, while the MBC value is 1.6% for both bacteria. The results of statistical tests on the diameter of the inhibition zone from the antimicrobial activity test against S. epidermidis and S. aureus, showed that there was a difference in the ability to inhibit bacterial growth between the positive control and the test concentration group of 2.5%, 5% and 10%. In the ratio of the inhibitory ability of bacteria at a spesific concentration, the test results showed that S. epidermidis bacteria had different bacterial growth inhibition abilities with S. aureus bacteria. Based on the results obtained, the ethanol extract of wole woe stems has potential as an antimicrobial.